Classic aircraft - Havers, John; Havers, Richard (Haynes Pub., 2009)
Aircraft have revolutionized the way we live. Billions of passengers take to the air every year and around the world airlines operate almost 80,000 flights daily. Many of the endeavors of the early aviation pioneers ended in heroic failure.